Capacity strengthening strategy through capacity needs assessment for Country Level Strategic Analysis and Knowledge Support System (SAKSS): Rwanda - Bizoza, Alfred R.; Rwirahira, John; Bizimana, Claude (International Food Policy Research Institute, 2014)
This study aims at assessing the capacity needs for different stakeholders involved in food and agricultural policy processes in order to develop a country specific capacity strengthening strategy to meet the strategic analysis and knowledge management needs of the Rwandan agricultural sector and rural development. Specifically the study intends to assess specific needs for strategic agricultural policy analysis and investment planning, monitoring and evaluation, and knowledge management in Rwanda. The study also seeks to identify what individual and organizational capacities are needed and to show how the existing capacities can be harnessed through their effective use in the organizations involved in the CAADP process. The study further highlights the current organizational and capacity constraints underpinning the policy process for the policy organizations to effectively play their role in meeting the objectives of CAADP. Finally, the study proposes a capacity development strategy for implementing SAKSS in Rwanda.